2020
DOI: 10.2147/jmdh.s247401
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Response to “Effect of Integrated Pictorial Handbook Education and Counseling on Improving Anemia Status, Knowledge, Food Intake, and Iron Tablet Compliance Among Anemic Pregnant Women in Indonesia: A Quasi-Experimental Study” [Letter]</p>

Abstract: We have carefully studied the article published under the title "Effect of Integrated Pictorial Handbook Education and Counseling on Improving Anemia Status, Knowledge, Food Intake, and Iron Tablet Compliance Among Anemic Pregnant Women in Indonesia: A Quasi-Experimental Study". 1 The results of this study had proven that counseling using a handbook that had been prepared by the researchers was really useful to increase knowledge, maintain adequate nutrition and prevent anemia in pregnant women, which was char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…O conhecimento sobre anemia avaliado neste estudo e por outros pesquisadores é necessário para tomar decisões no tratamento adequado. Um estudo de pesquisa antes e depois que mediu os conhecimentos dos médicos antes e depois da implementação de um programa de gerenciamento de sangue do paciente desenvolvido localmente fez concessões para a tomada de decisão clínica individualizada e descobriu que havia um aumento no conhecimento de que a anemia pré-operatória afetava adversamente a morbidade do paciente e mortalidade de 25% a 37% (Singh;Honnakamble;Rajoura, 2019;Abujilban;Hatamleh;Al-Shuqerat, 2019;Nugroho et al, 2020;Agustina et al, 2021).…”
Section: Discussionunclassified
“…O conhecimento sobre anemia avaliado neste estudo e por outros pesquisadores é necessário para tomar decisões no tratamento adequado. Um estudo de pesquisa antes e depois que mediu os conhecimentos dos médicos antes e depois da implementação de um programa de gerenciamento de sangue do paciente desenvolvido localmente fez concessões para a tomada de decisão clínica individualizada e descobriu que havia um aumento no conhecimento de que a anemia pré-operatória afetava adversamente a morbidade do paciente e mortalidade de 25% a 37% (Singh;Honnakamble;Rajoura, 2019;Abujilban;Hatamleh;Al-Shuqerat, 2019;Nugroho et al, 2020;Agustina et al, 2021).…”
Section: Discussionunclassified
“…Several previous studies have reported the effect of education on higher utilisation of services which were also reported in our study. 24,26 We still found that women been delivering at home. It is obvious to have complications during childbirth at home however we did not find many mothers with complications.…”
Section: Original Articlementioning
confidence: 99%
“…Based on the paths, and referring to similar problems, 3 , 4 we suggest that the authors carry out further analysis using path-analysis with Smart-PLS program because all independent variables are categorical data. 2 This method is expected to prove the status of age, education and gender as indirect factors of mental health of medical staff during the COVID-19 outbreak.…”
Section: Dear Editormentioning
confidence: 99%
“…3. Gender→ marriage→ mental health.For example, it is assumed that age affects marriage, then marriage affects mental health, as well as for other paths; and the authors can modify it.Based on the paths, and referring to similar problems, 3,4 we suggest that the authors carry out further analysis using path-analysis with Smart-PLS program because all independent variables are categorical data. 2 This method is expected to prove the status of age, education and gender as indirect factors of mental health of medical staff during the COVID-19 outbreak.…”
mentioning
confidence: 99%